Tools for Regulatory Quality and Financial Sector Regulation A Cross-Country Perspective - Black, Julia (OECD Publishing, 2009)
This report provides a comparative perspective on the application of quality regulation principles to financial sector regulators, in the US, Canada, Australia, the UK and France. The report compares key provisions of the codes of the Basle Committee and IOSCO, with the OECD's 2005 Guiding Principles for Regulatory Quality and Performance, and the 2009 Policy Framework for Effective and Efficient Financial Regulation (PFEEFR). The report analyses the independence and accountability of the regulators, as well as their powers. The analysis focuses on requirements for ex ante and ex post regulatory impact analyses, including burden reduction; for transparency and communication of decision making, as well as co-ordination and regulatory review; for improving the regulatory system over time and for regulating conflicts of interest. The report finds variation in the formal arrangements, and respective practices. It also finds that the requirements related to better regulation principles are often implemented too late in the decision-making process when regulations are set at the international level
Keywords: Governance